From Physical Inactivity to Exercise Maintenance; Barriers and Motivations : phenomenological research on personal training participants - Lindroos, Ruth (2018)
As the gap between those physically active and inactive continues to widen, one purpose for this study was to provide further understanding surrounding exercise behavior, particularly of those physically inactive. The issues at focus are perceived barriers and motivations towards exercising, in this case examined through personal- and weight training participation. In addition to previous research on the field, theories of the Transtheoretical Model (TTM) of behavior change and intrinsic and extrinsic motivations from the Self-Determination Theory (SDT) are used to support the analysis of the participants’ experiences. This research takes a phenomenological approach. The five previously physically inactive participants were individually interviewed using semi-structured interviewing, between October and December 2017. The study analyzes a selected phase of the participants’ lives, starting from physical inactivity and proceeding towards the maintenance of constant exercising. In addition to supporting the understanding of barriers and motivations to exercise, the research gives insight to the customer perspective behind personal training, on which completed research has only begun to appear during the last decade in Finland. Therefore, following the phase of their physical inactivity, the participants became long-term personal training customers. The results successfully identified a range of both common and uncommon perceived barriers to exercise of those physically inactive. Additionally, a motivational change between the beginning of exercise and its active maintenance was identified. Commonalities were found between the participants, from their experienced barriers to exercise, motivations to begin exercise and the motivational transformation towards long-term exercise. The participants had no contact with each other and lived in differing life stages. Previous research, the understanding of extrinsic and intrinsic motivations along with the timely stages of the Transtheoretical Model supported analyzing the exercise experiences at hand. Suggestions of future research include adapting the found barriers from this study to a larger scope of physically inactive individuals, in some cases lacking research on. It is suggested, that including the views of those who have experienced physical inactivity themselves should be taken to consideration in the promotion of physical activity and exercise. Likewise, gender differences in both barriers and motivations to exercise could be further investigated from a larger scope. Finally, the personal training industry remains to be a relatively new field of business in Finland, with a wide range of its aspects lacking research. Therefore, further studies on customer perspectives for its improvement could benefit the business in the future.